Macroeconomic dynamics and inflation regimes in the US: Results from threshold vector autoregressions - Martin Mandler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
This paper studies regime dependence in macroeconomic dynamics in the U.S. using a threshold vector autoregressive model in which endogenous regime switches are triggered by the inflation rate. The model separates a high from a low inflation regime with both regimes being strongly persistent. Generalized impulse response functions highlight important across-regime differences in the responses of the economy to monetary policy and inflation shocks. Simulating both regimes with individual structural equations interchanged shows a change in inflation dynamics to be the most important source of the transition of the U.S. economy from the high into the low inflation state while the change in the monetary policy reaction functions has only very little effect. Our results indicate that favorable changes in the economic structure and less frequent and smaller shocks are important explanations for the observed decline in U.S. macroeconomic volatility since the mid 1980s.
Keywords: E32; E58; C32; 330; threshold vector autoregression; Great Moderation; Konjunktur; Inflation; Makroökonomischer Einfluss; Geldpolitik; Schock; VAR-Modell; Schätzung; USA